The role of abo antibodies and molecular genotyping of blood group o in haemolytic disease of the foetus and newborn - Usman, Adiyatu Saidu (2013)
After the introduction of anti-D prophylaxis, the incidence of Rh haemolytic disease has decreased and ABO incompatibility between the mother and the fetus is now the leading cause of neonatal jaundice associated with blood group incompatibility. Neonatal ABO incompatibility occurs mostly in group A/B neonates delivered by group O mothers. The severity of haemolysis ranges from mild to severe with few neonates developing ABO haemolytic disease. Assessing and predicting the severity of haemolysis in neonates with ABO incompatibility and haemolytic disease has been carried out previously. This study was aimed at determining whether maternal IgG anti-A/B titre and blood group O molecular genotype can predict haemolysis in neonates with ABO HDFN. The severity of haemolysis was also assessed by determining the levels of haemolytic markers in neonates with ABO incompatibility. A total of 96 neonates with jaundice were enrolled in this study. Seventy were ABO incompatible (study group) and 26 (control group) were ABO compatible. Sixty mothers of the 70 ABO incompatible neonates and 30 mothers that were compatible (mother and neonate blood group O) with their neonates were studied for maternal IgG anti-A/B titre and ABO molecular genotype. Another 34 individuals who were blood donors were also studied for blood group O molecular genotype. The result obtained showed a significant difference (p<0.05) between the ABO incompatible and compatible groups in relation to the laboratory features that were used in assessing haemolysis. ABO incompatible neonates had higher levels of haemolytic markers compared to the ABO compatible neonates. Mode of delivery type of treatment required and level of haemoglobin were significantly different between neonates thad had ABO HDFN and does without HDFN. In neonates that had ABO HDFN, maternal IgG anti-A/B titre was a good predictor of haemolysis when carboxyhaemoglobin and absolute reticulocytes count were used as markers of haemolysis. No significant difference (p>0.05) was observed between the maternal IgG titre of ABO incompatible and compatible mothers. Of the 124 subjects that were typed for blood group O molecular genotype, only one had a different genotype which is 0102 but the remaining had O1O1. This study indicates that neonatal ABO incompatibility is associated with more haemolysis when compared with neonates with jaundice not caused by ABO incompatibility. Concentration of maternal IgG antibody titre is not affected by incompatible pregnancy even though maternal antibody titre can predict haemolysis. The major ABO molecular genotype of the O blood group in Malays is O1O1.